âTHE CHEAP PORTABLE RICE MILLâ SEBAGAI ALTERNATIF PENINGKATAN PEREKONOMIAN KELOMPOK USAHA TANI DI KELURAHAN KARANGMALANG - Meinarwati, Adelia Dini; Meisandy, Paulus; Sancoko, Damar; Wisnu, Nugroho (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Rice in a majority of states derived from rice fields of the countryside. However, the complicated problems of farmers in the countryside to erect manage their fields is the high cost of milling process that is happening in our network-based business group kelurahan Karangmalang. For that we make an effort ricemill machine to help kemompok farm. Ricemill machine itself is an existing machine with which we try to provide the innovation that is the process of combining paddy slep machine or a machine that is commonly called skinner with machine polishers paddy rice grain that has been peeled up quicker and practical in use. Specifications of this machine that is Model N-70-F with dimensions 112x44x74 cm. This machine has a capacity as large as 1100-1200 kg / hr with its size and rotational 10-11 KW 750-850 rpm and weighs 185 kg and Model HW60-A with dimensions 135x79x150 cm, this machine has a capacity as large as 1200 kg / hour with a force of 7 kw and 1,050 rpm spin machine size and weight of the machine 80 kg.